2010
DOI: 10.1111/j.1476-5381.2010.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signalling mediated through α7 and non‐α7 nAChR stimulation is differentially regulated in bovine chromaffin cells to induce catecholamine release

Abstract: BACKGROUND AND PURPOSE Ca2+ signalling and exocytosis mediated by nicotinic receptor (nAChR) subtypes, especially the a7 nAChR, in bovine chromaffin cells are still matters of debate. EXPERIMENTAL APPROACHWe have used chromaffin cell cultures loaded with Fluo-4 or transfected with aequorins directed to the cytosol or mitochondria, several nAChR agonists (nicotine, 5-iodo-A-85380, PNU282987 and choline), and the a7 nAChR allosteric modulator PNU120596. KEY RESULTS Minimal [Ca 2+]c transients, induced by low con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 56 publications
(67 reference statements)
2
49
1
Order By: Relevance
“…Additional evidence of D i states is found in a recent study measuring calcium currents evoked by nicotine, PNU-282987, and PNU-120596 in bovine chromaffin cells [150]. In this study, the authors were only able to detect an α-bungarotoxin (α-btx)-sensitive and PNU-120596-dependent increase in calcium response when low (1 μM) concentrations of nicotine were used to stimulate the cells.…”
Section: Positive Allosteric Modulation Of α7 Nachrmentioning
confidence: 58%
See 2 more Smart Citations
“…Additional evidence of D i states is found in a recent study measuring calcium currents evoked by nicotine, PNU-282987, and PNU-120596 in bovine chromaffin cells [150]. In this study, the authors were only able to detect an α-bungarotoxin (α-btx)-sensitive and PNU-120596-dependent increase in calcium response when low (1 μM) concentrations of nicotine were used to stimulate the cells.…”
Section: Positive Allosteric Modulation Of α7 Nachrmentioning
confidence: 58%
“…In this study, the authors were only able to detect an α-bungarotoxin (α-btx)-sensitive and PNU-120596-dependent increase in calcium response when low (1 μM) concentrations of nicotine were used to stimulate the cells. At concentrations of ≥ 3 μM nicotine, neither PNU-120596 nor α-btx had an effect on the response, indicating that the α7 component was lost by the higher nicotine concentrations [150]. To isolate and more closely examine the disappearing α7 component, varying concentrations of the α7 agonist PNU-282987 with 1 μM PNU-120596 were applied for 5 minutes to evoke a calcium response.…”
Section: Positive Allosteric Modulation Of α7 Nachrmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, an ␣-bungarotoxinsensitive and PNU-120596-dependent increase in calcium response from bovine chromaffin cells was only observed when low (1 M) concentrations of nicotine were used to stimulate the cells. At concentrations of Ն3 M nicotine, neither PNU-120596 nor ␣-bungarotoxin had an effect on the response, indicating that the ␣7 component was lost by the higher nicotine concentrations (del Barrio et al, 2011). In addition, when the ␣7 component of the total calcium response was isolated, increased concentrations of the ␣7 agonist N-(3R)-1-azabicyclo[2.2.2]oct-3-yl-4-chlorobenzamide (PNU-282987) with a fixed PNU-120596 concentration resulted in decreased ␣7-dependent calcium responses (del Barrio et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The source of the calcium increase would be mainly comprised of the calcium influx directly through the α7 nAChR itself (Fayuk & Yakel, 2007a; Gilbert et al , 2009), and any calcium-induced calcium release from intracellular calcium stores (Weisskopf & Nicoll, 1995; Sharma & Vijayaraghavan, 2003; Sharma et al , 2008). Although calcium influx through voltage-gated calcium channels (VGCC) previously was shown not to contribute significantly to the α7 nAChR-mediated presynaptic effect (Dickinson et al , 2008), other studies reported that calcium influx through VGCCs could contribute to some degree (Barrantes et al , 1995; Fayuk & Yakel, 2007b; del Barrio et al , 2011). In addition, recent studies showed that α7 nAChR activation enhanced NMDAR-mediated whole-cell currents and glutamate release from hippocampal synaptosomes (Zappettini et al , 2010; Li et al , 2013).…”
Section: Second Messenger Signaling Upon Activation Of α7 Nachrs-mentioning
confidence: 99%